On Application of Discrete Logarithms in Information - Hiding and Knapsack Problem with New Properties of Sk-Sets - Rizak AI-Rammahi, A.M.H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Discrete   logarithms  are applied      in many    cryptographic problems  . For instance ,   in public   key .  and for construction of sets with disti nct sums of  k-clcments.  The   purpose o r  this   paperis  to  modify  the  method ol' informationl1Â·iding  using        discrete logarithms  , introduce new properties of St - sets ,   uscdthe direct product   of    groups   to construct  cyclic group and finally, present modified   method   for   knapsack    problem using each of discrere logarithms and S,-sets.